On mixed discriminants of positively definite matrix - Zhao, Chang-Jian (Ars mathematica contemporanea, 2015)
In the paper, some new inequalities for the mixed discriminants of positively definite matrix are established, which are the matrix analogues of inequalities of the well-known mixed volumes function.
Keywords: Aleksandrov's inequality; mešane diskriminante; mešani volumen; mixed discriminants; mixed volume; neenakost Aleksandrova; simetrična matrika; symmetric matrix